Correlación entre SO2/FiO2 y PaO2/FiO2 en pacientes con insuficiencia respiratoria en ventilación mecánica - Ameghino Bautista, Jenny (2018)
ABSTRACT Introduction: Patients with mechanical ventilation respiratory insufficiency require strict control of parameters that indicate the presence of lung damage; One of the parameters is to assess the relationship between arterial pressure of oxygen and inspired fraction of oxygen, however, using other less invasive parameters is the current trend, such as oxygen saturation and inspired oxygen fraction. Objective: To determine the correlation between the oxygen saturation index / inspired fraction of oxygen and oxygen blood pressure / inspired fraction of oxygen in patients with respiratory insufficiency in a mechanical ventilator. Methods: An observational correlation study was performed in patients hospitalized in the Intensive Care Unit. The Pearson coefficient was measured between the variables arterial oxygen pressure / inspired fraction of oxygen and oxygen saturation / inspired fraction of oxygen at the beginning of the mechanical ventilator, at 24, 48 and 72 hours after the start of mechanical ventilation. Results: 180 samples from 45 patients were studied, it was found that the correlation between oxygen saturation / inspired fraction of oxygen and arterial pressure of oxygen / inspired fraction of oxygen at the beginning of mechanical ventilator was moderate with r = 0.64 p <0.001, however, the correlation tends to be stronger in the measurements of 24, 48 and 72 hours with values ​​of r = 0.67 p <0.001, r = 0.91 p <0.001 and r = 0.92 p <0.001 respectively. Proposing the following equation = oxygen arterial pressure / inspired fraction of oxygen = 0.8106 (oxygen saturation / inspired fraction) + 54.419. Conclusions: The use of the index of oxygen saturation / fraction inspired by the immediate period of use of MV, the correlation with arterial pressure of oxygen / inspired fraction is moderate, but after 24 hours of MV the correlation is strong. Non-invasive methods for the evaluation of oxygenation can be an alternative for clinical follow-up in patients with acute respiratory failure.